Criticism of legal protection for victims of drug abuse: the disharmony in legal substance regulation - Andri Winjaya Laksana; Hendro Widodo; Moh Aris Siswanto; H. D. Djunaedi; Setiawan Widiyoko (Legality : Jurnal Ilmiah Hukum, 2025)
This research aims to analyse the legal regulation of narcotics addicts in Indonesia and legal protection for victims of drug abuse, the disharmony in legal substance regulation.  Law Number 35 of 2009 concerning Narcotics in Indonesia establishes the legal framework for rehabilitation, protection and eradication of narcotics abuse at the national level. This regulation requires rehabilitation measures for narcotics users, especially those categorised as victims, and provides uniform law enforcement guidelines. On the other hand, regional regulations can expand and strengthen national regulations by adapting local approaches to suit the needs of local communities. This is legal research using qualitative research methods. Legal regulations for narcotics addicts in Indonesia are regulated in Law No. 35 of 2009 concerning Narcotics with a rehabilitative approach, but it still faces various challenges in its implementation. In Law No. 35 of 2009 concerning Narcotics, the disharmony of articles can arise due to several factors, including differing interpretations, unclear legal norms, or inconsistency with other relevant regulations. What is often debated is the different approaches between rehabilitation for narcotics addicts and criminal punishment for narcotics crime perpetrators in the Narcotics Law. Article 54 states that narcotics addicts are required to undergo medical and social rehabilitation. On the contrary, Article 127 paragraph (1) asserts that narcotics users without rights or against the law are subject to imprisonment.